Lack of ovarian skew in an allodapine bee and the evolution of casteless social behaviour. Issue 1 (2nd January 2018) - Dew, Rebecca M.; Tierney, Simon M.; Schwarz, Michael P.
Abstract : Facultatively social species exhibit varying degrees of reproductive skew that provide valuable insights into the possible evolutionary forces shaping the origins of obligate eusocial colony organisation, wherein the majority of individuals (workers) forgo direct reproduction. Here we report aspects of the nesting biology of a semi-arid population of the allodapine bee Exoneurella setosa, which forms social colonies that lack reproductive hierarchies and are therefore 'casteless'; an intriguing discovery given that a congeneric eusocial species exhibits the greatest morphological distinction between queen and worker castes in the entire subfamily Xylocopinae (Apidae). Exoneurella setosa exhibited a modal colony size of two females per nest and we analysed nest-mate differentiation in ovarian development, body size and wing wear (a proxy for foraging activity). We then contrasted empirical results with Monte Carlo-simulated colonies to ascertain that multifemale nests lack evidence for reproductive skew. Our results suggest that nest-site limitation is a key driver for eusocial organisation within the Xylocopinae and that the absence of such environmental limitations, combined with minor benefits for group nesting, can select for casteless social organisation.